1999
DOI: 10.1073/pnas.96.11.6558
|View full text |Cite
|
Sign up to set email alerts
|

The roles of prefrontal brain regions in components of working memory: Effects of memory load and individual differences

Abstract: Using an event-related functional MRI design, we explored the relative roles of dorsal and ventral prefrontal cortex (PFC) regions during specific components (Encoding, Delay, Response) of a working memory task under different memory-load conditions. In a group analysis, effects of increased memory load were observed only in dorsal PFC in the encoding period. Activity was lateralized to the right hemisphere in the high but not the low memory-load condition. Individual analyses revealed variability in activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
356
7
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 486 publications
(415 citation statements)
references
References 31 publications
50
356
7
2
Order By: Relevance
“…In the current study reductions in N100 amplitude with increasing memory load in young subjects may be attributable to memory load-dependent increases in inhibition from prefrontal cortex over auditory cortex. Consistent with this notion, studies in young subjects have shown increased activity in prefrontal cortex with increases in memory load (Braver et al, 1997;Jonides et al, 1997;Rypma and D'Esposito, 1999).…”
Section: N100 Activity During Memory Retrievalmentioning
confidence: 64%
“…In the current study reductions in N100 amplitude with increasing memory load in young subjects may be attributable to memory load-dependent increases in inhibition from prefrontal cortex over auditory cortex. Consistent with this notion, studies in young subjects have shown increased activity in prefrontal cortex with increases in memory load (Braver et al, 1997;Jonides et al, 1997;Rypma and D'Esposito, 1999).…”
Section: N100 Activity During Memory Retrievalmentioning
confidence: 64%
“…The Sternliquid crystal display screen positioned in front of their eyes. Participants berg task (Steinberg, 1966) used in the cur'ent study is a verbal working were instructed to hold two hand pads with their hands and to respond with memory task (Rypma & D'Esposito, 1999;Iypnia et al. 1999: Veltman et their thumbs (left or right) to "yes" or "no" (this order was randomized al.…”
Section: -/ As a Results Of 26-37 Hr Of Sleep Deprivation Individualmentioning
confidence: 99%
“…Participants viewed the set provided evidence that the left hemisphere i6 dominant for verbal processes of letters for 3 s (recognition). They then maintained this set in mind during Rypma & D'Esposito, 1999;Rypma ct al., 1999; E. F. a 7-s delay (retention). Subsequently, a probe letter was presented on the ; E.E Smith & Jonides, 1498, Veltman et al-, 2()03).…”
Section: -/ As a Results Of 26-37 Hr Of Sleep Deprivation Individualmentioning
confidence: 99%
“…Three event-related fMRI studies that manipulated memory load have failed to find that the delay period activity was affected by load [37,40,41]. For example, Jha and McCarthy [37] reported that remembering three faces did not evoke greater delay period activity in the DLPFC than remembering one face at any point during 15 or 24 s memory delays.…”
Section: Number Of Itemsmentioning
confidence: 99%
“…Increasing storage demands beyond capacity limits might invoke strategic changes in the way information is represented [44]. Rypma et al have argued [41,43] that the increased signal changes with increased load in the DLPFC are the consequence of the strategic process of data compression (e.g. chunking) because these effects are most prominent during the cue period when encoding takes place.…”
Section: Interpretation Of Load Effectsmentioning
confidence: 99%